Handwörterbuch des Altuigurischen Altuigurisch - Deutsch - Türkisch - Wilkens, Jens (Universitätsverlag Göttingen, 2021)
The "Concise Dictionary of Old Uyghur" is the first inventory of the entire vocabulary of Old Uyghur texts (manuscripts, block prints, inscriptions) found in the oasis cities of the ancient Silk Road (Turfan, Dunhuang and others). Also included is the rich loan vocabulary of Buddhist, Manichaean and Christian texts. With the help of the dictionary, editions of all text genres (religious, medical, astrological and divinatory texts, letters, deeds, contracts, inscriptions) can now be used for the first time without further lexicographic aids. The "Handwörterbuch des Altuigurischen" (Concise Dictionary of Old Uyghur) is particularly suitable for university teaching in the subject of Turkology, since even complex terms and collocations are covered. Because Old Uyghur is the best attested indigenous language of Central Asia in pre-Islamic times and at the same time the first extensively documented Turkic literary language, this variant of Old Turkic is of great importance not only for Turkology and general linguistics, but also for the diverse and still fascinating cultural history of the Silk Road. Translated with www.DeepL.com/Translator (free version)